Energy Efficiency in Subtropical Homes: Replacing Asbestos–Cement Roofs with Sustainable Alternatives - Manuel Saba; Oscar E. Coronado-Hernández; Leydy Karina Torres Gil (Buildings)
This study evaluates the impact of building orientation, typology, and envelope characteristics on energy efficiency and CO2 emissions in urban dwellings in subtropical climate, with a focus on Cartagena, Colombia. North-facing dwellings consistently demonstrate superior energy performance, achieving an average efficiency increase of 4.27 ± 1.77% compared to south-facing counterparts. This trend is less pronounced near the equator due to the sun’s high zenith angle. Semi-detached homes exhibit 23.17 ± 9.83% greater energy efficiency than corner houses, attributed to reduced exterior wall exposure, which lowers energy demand and CO2 emissions by 2.16 ± 0.74 kg CO2/m2 annually. Significant disparities in emissions are observed across socioeconomic strata; homes in strata 3 and 4 show the lowest emissions (6.69 ± 1.42 kg CO2/m2 per year), while strata 5 and 6 have the highest (10.48 ± 1.42 kg CO2/m2 per year), due to differences in construction quality and glazing ratios. Roofing materials also play a key role, with thermoacoustic (TAC) roofs reducing emissions by up to 5.80% in lower strata compared to asbestos–cement roofs. Furthermore, sandwich panels demonstrate substantial potential, achieving CO2 emissions reductions of up to 51.6% in strata 1 and 2 south-facing median homes and a minimum saving of 9.4% in strata 5 and 6. These findings underscore the importance of integrating energy performance criteria into public housing policies, promoting construction practices that enhance sustainability and reduce greenhouse gas emissions while improving occupant comfort and property value.